2018
DOI: 10.4172/2165-7556.1000232
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mobile Phone Addiction on Procrastination: A Moderated Mediating Model

Abstract: As technologies advances, mobile phones, especially smartphones become increasingly dispensable for young adults, it is particularly prevalent among universities students. But the tools negatively affect the users' physical and mental health who spend more time on it, such as interpersonal communication problems poor sleep quality, and academic failure. The recent papers pointed out that a prominent association among mobile phone addiction, future time perspective, procrastination each other, but few authors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Similarly, the mediating role of past negative and present fatalistic TP orientations was found in the relationship between ADHD symptoms and addictive Facebook use (Settanni et al, 2018). The present study significantly broadens the findings of earlier research (Liu et al, 2018) by considering future anxiety, one of the aspects of future time perspective, in explaining online addiction.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Similarly, the mediating role of past negative and present fatalistic TP orientations was found in the relationship between ADHD symptoms and addictive Facebook use (Settanni et al, 2018). The present study significantly broadens the findings of earlier research (Liu et al, 2018) by considering future anxiety, one of the aspects of future time perspective, in explaining online addiction.…”
Section: Discussionsupporting
confidence: 78%
“…Future time perspective acts as a buffer against two types of addiction: Facebook and Internet addictions (Przepiorka & Blachnio, 2016). A recent study (Liu et al, 2018) showed that future time perspective partially mediated the relationship between mobile phone addiction and arousal and avoidant procrastination. The study investigated the positive dimension of future time perspective, comprising domains such as behavioral commitment, future efficacy, far goal orientation, future intention, and consciousness of purpose.…”
Section: Future Anxiety As a Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…From another perspective, PMPU can be considered an antecedent for procrastination (Liu, Gao, Shu, & Cheng, 2018;Wang et al, 2019;Zhen et al, 2020). In particular, PMPU resembles mobile phone addiction or Internet addiction, which has been found to induce changes in the brain system and disrupt the functions of the prefrontal cortex that are responsible for self-control capacity (He, Hong, Bao, & Lei, 2012;Lewis, 2017).…”
Section: The Direct and Indirect Effect Of Pmpu On Academic Procrasti...mentioning
confidence: 99%